The voice of the characters: teaching the use of reported speech in the primary school - Claudia Borghetti; Stefania Ferrari; Letizia Lazzaretti; Gabriele Pallotti; Greta Zanoni (Italiano a scuola, 2019)
This paper presents the results of a study conducted on the written narratives of two fifth-grade primary school classes involved in the project Observing the Interlanguage. The aim was evaluating the effects of a pedagogical intervention in which the pupils were guided to observe the linguistic-discursive properties of oral and written texts (literary and produced by the students themselves) on their choices regarding the use of reported speech. The results show that children in the experimental classes write more vivid narratives than their peers in two control classes, because of their greater use of direct speech. The study demonstrates the effectiveness of pedagogical interventions which give pupils an active role as “little researchers" and involve them in collaborative tasks of observation and manipulation of their own and others' texts.